(untitled) (Colloquia Comparativa Litterarum, 2025)
The paper opens by briefly outlining the development of women’s literature in the ex–East European countries since 1989. Then it turns to feminist literary theory, tracking two different periods of its reception by and adaptation to literary criticism in post-communist academic research. The concepts of women’s generations and women’s literary canon, vital for the Western tradition of gynocriticism, are closely analyzed in relation to their relevance to present-day women’s literature in post-communist culture. The paper closes by outlining a threefold model of the perspective from which to speak of women’s literature embedded in, or in counter-stance to, the traditional literary canon.